Scurvy mimicking juvenile idiopathic arthritis in two pediatric patients - B Harikrishnan; Suma Balan (Indian Journal of Rheumatology)
Scurvy, though previously reported from developing countries, is now being increasingly reported from developed countries. Although rare in pediatric population, it is well known to cause lower-extremity pain and refusal to walk in children. Here, we summarize two cases of scurvy in young children who presented with difficulty to walk. Both of them came with a provisional diagnosis of oligoarticular juvenile idiopathic arthritis. The first case underwent extensive evaluation before the diagnosis of scurvy was made. Dietary histories eventually revealed that both had limited intake of fruits and vegetables, as first patient existed on a diet of milk products and a nutritional supplement provided by the state government. The second patient had autism. Radiographic changes of long bones were observed in both patients. Both of them had a Vitamin C level of <0.1 mg/dl. After replacement with Vitamin C, both patients recovered and started to walk again. This case series highlights the importance for rheumatologists to have a higher index of suspicion for scurvy in children presenting with pain and difficulty to bear weight.